Self-portrait with a swarm of bees - Wagner, Jan, 1971- (Speech and silence box set collection, 2019)
This pocket-sized paperback is one of the thirty titles published for 2019 Hong Kong International Poetry Nights. The theme of IPHHK2019 is Speech and Silence. From 19-24 November 2019, 30 invited poets from various countries will be in Hong Kong to read their works based on the theme Speech and Silence. Included in the anthology and box set, these unique works are presented with Chinese and English translations in bilingual or trilingual formats.